(untitled) (MAUSAM, 1989)
Week by week assured rainfall at different probability 1evels90-10% has been computed for 103 stations of Tamilnadu by fitting incomplete Gamma distribution model. This assured rainfall has been used to demarcate the dry farming tract of Tamilnadu into various homogeneous rainfall zones the analysis has brought out 4 homogeneous rainfall pattern zones. Important features noticed In assured rainfall distribution at different probability levels have been discussed. The drought prone area and a high assured rainfall pattern zones of this state have also been identified. The table and diagrams presented in this paper should be found useful for identifying broad crop prospects in different areas of the State.